Extracellular polymeric substances from soil-grown bacteria delay evaporative drying. (February 2023) - Benard, Pascal; Bickel, Samuel; Kaestner, Anders; Lehmann, Peter; Carminati, Andrea
Highlights: Soil water evaporation can be delayed by the complex biofilm producer B. subtilis . An accelerated retreat of the evaporation front initiates decelerated water loss. Reduced soil hydraulic conductivity and surface tension explain the process. Modifications are result of a continuous adaptation. Abstract: When soils dry, water flow and nutrient diffusion cease as the hydraulic microenvironments vital for soil life become fragmented. To delay soil drying locally and related adverse effects, bacteria and plants modify their surroundings by releasing extracellular polymeric substances (EPS). As a result, the physical properties of hotspots like biological soil crusts or the rhizosphere differ from those of the surrounding bulk soil. Specifically, the presence of EPS delays evaporative soil drying. Despite the evidence of reduced evaporation from EPS-amended soils, the mechanisms controlling soil water content dynamics remain elusive. Thus, our study aimed to elucidate the potential of bacteria to modify their local environment when exposed to oscillations in soil water content induced by evaporative drying. We incubated sand microcosms with two contrasting strains of Bacillus subtilis for one week in a flow cabinet. At the end of the incubation period, local water loss was quantified and spatially resolved using time-series neutron radiography. Strain NCIB 3610, a complex biofilm producer steadily modified soil evaporation dynamics during the incubation period resulting in a substantial delay in soil drying due to hydraulic decoupling of the evaporation front from the soil surface. Evaporation dynamics remained largely unaltered in the microcosms inoculated with the domesticated strain 168 trp + compared to the control treatment. The mechanism of hydraulic decoupling induced by NCIB 3610 was verified by estimates of diffusive fluxes and the position of the evaporation plane in the microcosm. Additionally, the role of polymeric substances in hydraulic decoupling was confirmed by an evaporation experiment using xanthan as an EPS analogue.